Glycaspis brimblecombei Moore, 1964 (Hemiptera: Psyllidae) on eucalyptus: oviposition non-preference and antibiosis - Ribeiro, Zulene Antonio [UNESP]; Sardinha de Souza, Bruno Henrique [UNESP]; Costa, Eduardo Neves [UNESP]; Petrilli Mendes, Jose Eduardo; Mafia, Reginaldo Goncalves; Boica Junior, Arlindo Leal [UNESP] (Springer, 2015)
Forest plantations with Eucalyptus spp. (L'H,r) in Brazil are highly yielding. However, this activity is more and more threatened due to interactions with phytophagous insects, especially by exotic species, such as the red gum lerp psyllid Glycaspis brimblecombei Moore (Hemiptera: Psyllidae). This study aimed to evaluate the resistance in eucalyptus against the psyllid in oviposition and biological development assays, attempting to identify potential genotypes resistant to the pest for forest plantations. In addition, we tested the hypothesis of that concentration of total phenolics and lignin, and amount of epicuticular wax were associated with the expression of resistance. Results showed that there was variation in the levels of resistance among the genotypes assessed. Oviposition non-preference was observed on Eucalyptus citriodora (Hook) in free-choice and no-choice tests, and Clone FP10 was least preferred in the no-choice test. The genotypes E. citriodora and Clone FP6 provided 100 % nymphal mortality, and Clones FP7 and FP9 also affected negatively the G. brimblecombei development by lengthening the duration of the nymphal stage and reducing adult emergence. Clone FP6 had higher concentration of total phenolics and larger contact angle formed between the water droplet and leaf surface, which may be associated with thicker layer of epicuticular wax on the leaves, and one of the causes of high nymphal mortality. Thus, the use of the resistant genotypes of eucalyptus screened against G. brimblecombei is a promising and viable alternative for forest plantations infested with this pest.
Keywords: Epicuticular wax; Forest plantation; Lignin; Phenolics; Red gum lerp psyllid